Sexually Transmitted Diseases: A Significant Complication of Childhood Sexual Abuse - Deborah Lindsay; Joanne Embree (Canadian Journal of Infectious Diseases)
The acquisition of one or more sexually transmitted diseases (STD) is a significant complication of sexual assault of children. The risk of infection by pathogens varies from less than 1 to 50% depending on the nature of the assault, the organism studied and the background prevalence of STD in the general community. The correct diagnosis of STD in children depends upon optimal collection and appropriate laboratory testing of clinical specimens. Diagnosing STD will allow for treatment and follow-up to ensure cure of these infections as well as to monitor for re-infection. It will also help confirm that sexual activity involving the child has occurred. This can be exi.remely important, particularly when there are minimal other physical findings of abuse or if the child has limited verbal skills and thus cannot provide a complete disclosure. All physicians who care for children should be knowledgeable about the methods of STD diagnosis and the currently recommended treatment regimens.